The Understanding and Practice of Karuna from Selected Buddhist Institutions - Najiah Athirah Jamaludin; Mohd Nor, Nur Suriya; Zainal Abidin, Sarah Hamizah (Advances in Humanities and Contemporary Studies, 2025)
This study explores the understanding of karuṇā (compassion) among selected Buddhist institutions in the Klang Valley, Malaysia. Using qualitative methods, including in-depth interviews and focus group discussions, the research engaged leaders, committees, and volunteers from Sam Poh Thong Temple and the Shah Alam Buddhist Society. Findings reveal that participants conceptualize karuṇā as a universal compassion, a core Buddhist teaching, and an integral element of the Four Brahmavihāras. Their interpretations emphasize its association with wisdom (prajñā) and its cultivation through meditation, reflection, and lived experience. The institutions articulate karuṇā not only as an ethical principle but also as a guiding framework for community engagement, family well-being, and environmental consciousness. Variations in depth of understanding were noted, with leaders demonstrating more comprehensive knowledge, while volunteers often relied on personal experiences or external learning. Nevertheless, across both institutions, karuṇā was consistently regarded as central to Buddhist identity and as a transformative value for fostering harmony and reducing suffering in society. This research contributes to a deeper comprehension of how Buddhist institutions in Malaysia internalize and articulate the meaning of compassion within their religious and social contexts.